Microwave assisted synthesis of Schiff base via bioplatform chemical intermediate (HMF) derived from Jatropha deoiled seed cake catalyzed by modified Bentonite clay. (2017) - Surendra, B.S.; Veerabhadraswamy, M.
Abstract: A novel route for Jatropha de-oiled seed cake (DSC) treatment has been developed for the synthesis of valuable intermediate (HMF) by acid activated Bentonite clay catalyst. Hydrolysis of the deoiled seed cake with different concentrations of H2 SO4 activated clay (0.1M - 3M) was studied under microwave irradiation and obtained 5-HMF product was analyzed by GC-MS, UV Visible and FT-IR studies. Insitu reaction of intermediate with aniline forms solid Schiff's base product and has been confirmed by FT-IR analysis. The prepared acid activated clay catalysts were characterized by PXRD, BET and FT-IR spectral analysis. PXRD studies revealed that the changes of phase and average crystallite size (11-18 nm). The present work directs the possibilities to provide some new insights into the synthesis intermediate from non edible de-oiled seed cake with high activity for environmental clean-up.